Distribution, Infestation and Occurrence of Noorda blitealis Wlk. and Gitona distigma (Meigen) in Moringa oleifera Lam. in the Home Gardens of Jaffna District, Sri Lanka - Sharjana, K.; Mikunthan, G. (University of Jaffna, 2018)
Moringa oleifera Lam. is grown in Jaffna home gardens for pods and leaves. After the introduction of PKM 1 Moringa variety, the populations of leaf eating caterpillar (Noorda blitealis Wlk.) and pod fly [Gitona distigma (Meigen)] were suddenly increased causing severe damage in leaves and pods, respectively. Hence, this study was carried out to map the distribution of the insects and their occurrence in Jaffna District. The infestation of N. blitealis was reported in Maruthankerny, Velanai, Karaveddy, Chavakachcheri, Pointpedro, Kaytes, Nallur, Kopay, Kaithady, Jaffna, Uduvil, Thellipalai, Sandilipay and Chankanai Divisional Secretariat (DS) divisions. High infestation score of 4 (defoliation 76% -100%) was recorded in Maruthankerny, Velanai, Karaveddy, Chavakachcheri and Point Pedro DS divisions. G. distigma infestation was observed in Maruthankerny, Velanai, Chavakachcheri and Karaveddy DS divisions. The highest score of 4 (pod damage 76 -100%) was reported in Maruthankerny, Karaveddy and Velanai DS divisions. The caterpillar, N. blitealis larvae fed on the leaves and barks. It webbed, skeletonised and defoliated the tree completely. The pod fly, G. distigma maggots were found feeding in tender pods. The affected pods dried and split from the tips. Gummy exudates were found oozing out from the pods. A questionnaire survey carried out among Moringa growers in this district revealed that N. blitealis infestation increases in the rainy season during the months of October, November, December, January and February. Families used sanitary measures (92%), pruning (92%), hand picking (84%) and application of ash (33%), leaf extracts (25%), cow urine (16%) and insecticides (32%) to manage N. blitealis in their home gardens. Spacing of the plants showed a negative correlation and fertilizer application had a positive correlation with the severity of N. blitealis. Spiders, Chrysoperla carnea, Cydonia vicina, mantis and Centropus sinensis were recorded as predators on N. blitealis. Creating awareness among the public on these pests and their damage will help identify the pests easily and will also help to manage the problem using non-chemical means.
Keywords: forage-value; growth-stages; leaf weight; nutrient composition